FROM THE INSTITUTE TO THE UNIVERSITY: DIRECTIONS OF THE PSYCHOLOGICAL AND PEDAGOGICAL RESEARCH IN NIZHNY NOVGOROD STATE PEDAGOGICAL UNIVERSITY IN THE LATE XX - EARLY XXI CENTURIES - N. V. Shutova; V. V. Kisova (Вестник Мининского университета, 2017)
The article presents a historical overview of the development of psychological education and the main directions of psychological research in Nizhny Novgorod State Pedagogical University. In the present study we examine the main research areas of psychological and pedagogical research modernization and specificity of psychological education in NSPU since 90-ies of the XX century to the present day. The authors give a comprehensive overview of the features of deep formation of the system of psychological training of personnel for public education, as well as consider the dynamics of scientific capacity-building of the Pedagogical University. The work of the Dissertation Council of Psychology and the results of its operations at the university for more than twenty years of existence are analyzed. It provides the most important scientific works of faculty members who have made a significant contribution to the development of psychological science in Russia. The article mark the scientific results achieved by teams of psychological faculties at the present stage and promising innovative directions of psychological research work of the teaching staff.